2015
DOI: 10.1194/jlr.p059477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic meta-analysis of 15,901 African Americans identifies variation in EXOC3L1 is associated with HDL concentration

Abstract: and replication). EXOC3L1 is strongly expressed in vascu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…For comparability with traditional GWAS, we evaluated results from stage 1 main effect models. Of the 356 previously reported associations for 279 variants (compiled from 16,12 ), there were 236 associations for 189 variants that were confirmed in our data (consistent direction and p < 0.05/356), for a 66.3% concordance rate (Supplementary Table 17).…”
Section: Resultssupporting
confidence: 86%
“…For comparability with traditional GWAS, we evaluated results from stage 1 main effect models. Of the 356 previously reported associations for 279 variants (compiled from 16,12 ), there were 236 associations for 189 variants that were confirmed in our data (consistent direction and p < 0.05/356), for a 66.3% concordance rate (Supplementary Table 17).…”
Section: Resultssupporting
confidence: 86%
“…Additionally, when testing replication of SNPs previously identified in groups other than non-Hispanic whites, we generally found that the meta-analysis of all GERA groups provided consistent evidence of replication, and performed better than using the much smaller ancestry-matched group. In the GERA meta-analysis, 2/2 lead SNPs first identified in African Americans 7 , 12 replicated, 4/5 Japanese 11 and Chinese 64 SNPs replicated, and 26/34 SNPs in Mexicans 10 /Hispanics 5 replicated.…”
Section: Discussionmentioning
confidence: 99%
“…For replication of previously-reported loci, we first considered the loci from GLGC 3 , 4 , but favoring the refinements from 20 (when exome-wide significant) and 16 , 18 plus additional novel loci from several studies 5 10 , 12 15 , 17 , for a total of 189 loci (defined here as non-overlapping 1Mb windows, using the most significant p-value for the lead SNP, and collapsing 1Mb windows with R 2 >0.3, which merged only one window). Of these, 185 were available to test.…”
Section: Methodsmentioning
confidence: 99%
“…Larger genome-wide studies of African ancestry individuals are needed. Additionally, careful consideration of linkage disequilibrium structure differences across ancestries can yield new insights in previously identified regions[87, 93]. …”
Section: Genomic Influences On Interethnic Differences In Serum Lipidsmentioning
confidence: 99%